Chlorine-based dry etching of β-Ga2O3 - Hogan, Jack E; Kaun, Stephen W; Ahmadi, Elaheh; Oshima, Yuichi; Speck, James S (Semiconductor science and technology, 2016)
Reactive ion etching (RIE) and inductively coupled plasma (ICP) etching techniques were used to determine the optimal dry etch conditions for β-Ga2O3. RF power and chamber pressure were examined to study their effects on etch rate and surface roughness for three crystallographic planes, i.e., (100); (010); and ( 2 ¯ 01 ) by RIE. BCl3 etch rate calibrations were performed on all β-Ga2O3 planes studied, in comparison to Cl2. RIE yielded moderate etch rates (<20 nm min−1), and surface roughness showed no clear trend with RF power. Moreover, the effect of bias power, plasma power, and the choice of etchant were studied using ICP. The etches performed by ICP were shown to be superior to RIE in both etch rate and surface roughness, due to the much higher plasma densities and uniformities possible with plasma powers beyond those realized in RIE. The maximum etch rate of 43.0 nm min−1 was achieved using BCl3 in ICP. SF6 BCl3 mixtures, which yield high GaN etch rates, were also studied. However, in contrast to GaN etching, SF6 BCl3 was found to be far less effective than pure BCl3 in etching β-Ga2O3.